2016
DOI: 10.1155/2016/2576496
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Pericardial Effusion with Tamponade: A Rare Adverse Effect of Infliximab—Case Report and Literature Review

Abstract: Introduction. Antitumor necrosis factor (TNF) alpha agents are commonly used biologic therapies for a wide variety of rheumatic and inflammatory diseases. Here, we present a case of hemorrhagic pericarditis as a consequence of infliximab and review the literature on pericardial complications stemming from this drug class. Methods. For the literature review, search terms using versions of antitumor necrosis factor alpha AND pericardial effusion OR pericarditis OR pleuropericarditis OR cardiac tamponade were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The diagnosis of drug‐induced pericarditis is often difficult. Typical symptoms include dyspnoea, fever, chest pain and cough and can be associated with leukocytosis and markedly elevated C‐reactive protein miming viral or bacterial aetiology . Additionally, patients on infliximab are at increased risk of infection because of drug‐related immunosuppression.…”
Section: What Is Known and Study Objectivementioning
confidence: 99%
“…The diagnosis of drug‐induced pericarditis is often difficult. Typical symptoms include dyspnoea, fever, chest pain and cough and can be associated with leukocytosis and markedly elevated C‐reactive protein miming viral or bacterial aetiology . Additionally, patients on infliximab are at increased risk of infection because of drug‐related immunosuppression.…”
Section: What Is Known and Study Objectivementioning
confidence: 99%
“…The treatment of ATIL is based upon the cessation of the offending agent. In severe cases, steroids and immunosuppressive agents have also shown to be effective [2]. Alternate therapy is then chosen for the underlying immunological or rheumatological disorder, which in our patient was Ulcerative Colitis.…”
Section: Discussionmentioning
confidence: 94%
“…Pericardial effusions have been reported as a possible adverse effect of TNF-α inhibitor use [69]. Soh et al reported 2 cases of pericardial effusions in patients on TNF-α therapy, both with surgical drainage.…”
Section: Discussionmentioning
confidence: 99%